Effect of non-surgical periodontal therapy on salivary and gingival crevicular fluid concentration of visfatin in periodontal health and disease - Hira Ismail; Anjani Kumar Pathak; Nand Lal; Pavitra Rastogi; Kaleem Ahmad; Mohd. Aamir Khan (Journal of Oral Biology and Craniofacial Research)
Background and objective: Visfatin, a pleotropic mediator mostly produced by visceral fat, is crucial in controlling the immunological and defensive systems. It serves the roles of a cytokine, an enzyme involved in energy metabolism, and a growth factor. The objective of the present study was to assess the impact of non-surgical periodontal therapy (scaling and root planing) on visfatin concentrations in saliva and gingival crevicular fluid in individuals with Periodontitis (stage-II grade-A) Materials and methods: 54 individuals were divided into Group A (Periodontally Healthy) and Group B1(Periodontitis baseline) based on periodontal parameters including plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), and radiographic parameters. After NSPT (SRP), Group B1 patients were recalled after 4 weeks, constituting Group B2 (post NSPT group B1). At baseline and 4 weeks after non-surgical periodontal therapy (SRP), all clinical parameters, salivary and GCF samples were recorded. An ELISA kit was used to measure the levels of visfatin. Using the paired t-test, unpaired t-test, and Pearson's correlation coefficient, data were analysed using SPSS 15. Results: After non-surgical periodontal treatment (SRP), the mean salivary and gingival crevicular fluid concentration of visfatin considerably decreased to a level comparable to periodontal health. In all groups, GCF visfatin concentration was higher than salivary concentration of visfatin. In periodontitis patients, visfatin concentration in GCF was 1.5 times higher than in saliva. Conclusion: The results of this investigation suggest a direct correlation between salivary and gingival crevicular fluid visfatin concentration and periodontal tissue inflammation and disease activity.